AVENUE21. Planning and Policy Considerations for an Age of Automated Mobility - Mitteregger, Mathias; Bruck, Emilia M.; Soteropoulos, Aggelos; Stickler, Andrea; Berger, Martin; Dangschat, Jens S.; Scheuvens, Rudolf; Banerjee, Ian (Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2023)
Across the world, advances are being made in the development of connected and automated mobility. At first it was expected that the technology would make a positive contribution to many traffic-related problems: from increasing road safety and reducing greenhouse gas emissions to freeing up space and making streets more appealing as public spaces. However, these effects are by no means guaranteed - by contrast: it is becoming increasingly clear that the introduction of this technology must be well managed if the anticipated benefits are to be achieved. Based on the results of the four-year research project AVENUE21 at the TU Wien, this volume brings together the findings of international authors. Divided into four topic areas - mobility and transport, public space, spatial development and governance - various perspectives as well as example applications and planning solutions related to connected and automated mobility are described in a global context. The result that emerges is an overview of international approaches to how automated driving systems can be introduced in a targeted manner in the interests of sustainable mobility and settlement development while also taking into account current (local) challenges. The volume thus complements previous studies by asking not what impacts connected and automated vehicles will have, but rather for what purpose, where and in what form connected and automated mobility is actually needed. About the editors: The research on which this book is based was conducted by an interdisciplinary team at the Faculty of Architecture and Spatial Planning at the TU Wien together with international experts. The research project AVENUE21 was funded as Ladenburg Kolleg by the Daimler and Benz Foundation.